Mongolia : Fifth Review Under the Extended Fund Facility Arrangement and Request for Modification and Waiver of Applicability of Performance Criteria-Press Release; Staff Report; Staff Supplement; and Statement by the Executive Director for Mongolia. (IMF Staff Country Reports; Country Report ;, 2018)
A three-year arrangement for Mongolia under the Extended Fund Facility (EFF) was approved on May 24, 2017, in an amount equivalent to SDR 314.5054 million (435 percent of quota, or about USD 425 million). The arrangement is part of a USD 5.5 billion multi-donor financing package that supports the authorities' Economic Recovery Plan. The extended arrangement is subject to quarterly reviews.